Islam and Local Culture: The Peril of State Violence and Hallyu Fandom in Indonesia (With Reference to Palestine) - Oh, Ingyu (Archīum Ateneo, 2024)
The invasion of Hallyu (or the Korean Wave) subculture in Indonesia created a new pattern of gendered cultural consumption in the largest Islam country in the world. The most ardent Hallyu supporters in Indonesia are women who are organizing massive urban fan gatherings, K-pop concerts, and group tours to Seoul. With a long and devastating record of state violence on Marxists, Chinese, and women in general, current public tolerance to Hallyu by the Indonesian government seems flimsy as female Hallyu fandom is threatening the mainstream Islamic value of feminine subservience. Although the strength of the local culture vis-à-vis Islam in Indonesia allowed an easy invasion of Hallyu into the country, the gender divide in the consumption of Hallyu is providing the Islam leaders with an easy excuse for possible state violence against women. Unlike Islamic, Western, and Japanese culture that are widely popular in the country, Hallyu’s salient feminine following invites jealous and alarmed reactions from Indonesian Muslim males. As the Japanese and Chinese anti-Hallyu sentiments among the male population led to massive outbreaks of anti-Korean hate speeches and demonstrations against the Korean residents and Hallyu promoters in the two countries, this paper analyzes how the female fans in Indonesia and Palestine are reacting to such threats.